Assessment of left ventricular function long term after arterial switch operation for transposition of the great arteries by dobutamine stress echocardiography. Issue 1 (16th December 2004) - Hui, L; Chau, A K T; Leung, M P; Chiu, C S W; Cheung, Y F
Abstract : Objectives: To use dobutamine stress echocardiography to determine left ventricular (LV) function and wall motion of children long term after arterial switch operation (ASO) for transposition of the great arteries. Design and patients: 31 patients (24 boys) with ASO performed at a mean (SD) of 15.5 (4.3) days of life were studied at an age of 9.4 (2.0) years. All had normal coronary angiographic findings. LV echocardiographic indexes, including fractional shortening, ejection fraction, rate corrected velocity of circumferential fibre shortening (VCFc), and wall stress, as well as LV wall motion abnormalities were determined at rest and under dobutamine stress. The results were compared with those of 20 healthy age matched control participants. Setting: Tertiary paediatric cardiac centre. Results: Fractional shortening, ejection fraction, and VCFc were significantly lower in patients than in controls at rest (all with p < 0.001). Stress–velocity index detected impaired LV contractility in 19 (61%) patients at rest. An older age at operation (p  =  0.01), longer bypass (p  =  0.01) and circulatory arrest times (p  =  0.045), and an unusual coronary artery pattern (p  =  0.059) were associated with impaired resting LV contractility. Dobutamine stress echocardiography unmasked wall motion abnormalities in 23 (74%) patients. Exercise myocardial perfusion scan, performed in 22 patients, showed reversible myocardial perfusion defects in 17. These defects corresponded to segments of hypokinesia as detected by dobutamine stress echocardiography. Conclusion: A significant proportion of children, albeit asymptomatic, had impaired baseline LV contractility and reversible myocardial perfusion defects and mild wall motion abnormalities on stress after ASO.